Effects of ozone therapy on anxiety and depression in patients with refractory symptoms of severe diseases: a pilot study - Clavo, Bernardino; Cánovas-Molina, Angeles; Díaz-Garrido, Juan A.; Cañas, Silvia; Ramallo-Fariña, Yolanda; Laffite, Horus; Federico, Mario; Rodríguez-Abreu, Delvys; Galván, Saray; García-Lourve, Carla; González-Beltrán, Damián; Caramés, Miguel A.; et al. (Frontiers in Psychology, 2023)
1) Background: Patients with refractory symptoms of cancer treatment or advanced chronic nononcologic diseases frequently experience anxiety, depression, and an altered health-related quality of life (HRQOL). Usually, this status becomes a vicious circle of complex management for patients, families, and healthcare providers. Some publications have described the beneficial effect of ozone therapy on this kind of patient. The aim of this study was to preliminarily evaluate the impact of ozone therapy on self-reported anxiety and depression in patients with refractory symptoms of cancer treatment and advanced nononcologic diseases. 2) Methods: Before and after ozone treatment, we assessed i) anxiety and depression according to the Hospital Anxiety and Depression Scale (HADS); ii) the HRQOL (according to the EQ-5D-5L questionnaire), which includes a dimension on anxiety and depression and a visual analog scale (VAS) measuring self-perceived general health. 3) Results: Before ozone therapy, 56% of patients were on anxiolytic and/or antidepressant treatment. Before and after ozone therapy, the anxiety and depression HADS subscales i) significantly correlated with the anxiety/depression dimension of the EQ-5D-5L questionnaire and ii) inversely correlated with the health status as measured by the VAS. After ozone therapy, we found a significant improvement in anxiety and depression measured by both the i) HADS subscales and ii) EQ-5D-5L questionnaire. 4) Conclusions: The addition of ozone therapy for patients with refractory symptoms of cancer treatment and advanced chronic nononcologic diseases can decrease anxiety and depression severity levels. Additional, more focused studies are ongoing to provide the needed explanatory information for this finding.